PENGARUH UKURAN PERUSAHAAN DAN PROFITABILITAS PADA AUDIT DELAY DENGAN REPUTASI KAP SEBAGAI VARIABEL PEMODERASI - Ari Murti, Ni Made Dwi; Widhiyani, Ni Luh Sari (E-Jurnal Akuntansi, 2016)
Audit delay is the time span that indicates the length of auditor completed the audit work. Company size and profitability is the one factors that affect on audit delay, but these factors have an not consistent influence, and allegedly it is moderated by firm's reputation. The purpose of this study was to determine the effect of company size and profitability on audit delay with the public accounting firm's reputation as a  moderating. This study was performed on manufacturing companies listed in Indonesia Stock Exchange in 2012-2014. The number of samples is 66 companies with 198 observations. Sample is determined by purposive sampling method. The data used are secondary data in the form of financial statements. Data collected by non-participant observation method. The analysis technique used is Moderated Regression Analysis. The results showed that company size and profitability have negative effects on audit delay. Public accounting firm’s reputation proved to moderate the effect of company size and profitability on audit delay .
Keywords: audit delay; company size; profitability; public accounting firm’s reputation; moderation